Răspunsuri

2014-10-23T07:16:04+03:00
700 - [ 400 - ( 300 - x ) ] = 500
400 - ( 300 - x ) = 700 - 500
400 - ( 300 - x ) = 200
300 - x = 400 - 200
300 - x = 200
x = 300 - 200
x = 100

600 - [ 300 - ( 25 + x ) ] = 425
300 - ( 25 + x ) = 600 - 425
300 - ( 25 + x ) = 175
25 + x = 300 - 175
25 + x = 125
x = 125 - 100
x = 25
700 - [ 400 - ( 300 - x ) ] = 500
400 - ( 300 - x ) = 700 - 500
400 - ( 300 - x ) = 200
300 - x = 400 - 200
300 - x = 200
x = 300 - 200
x = 100

600 - [ 300 - ( 25 + x ) ] = 425
300 - ( 25 + x ) = 600 - 425
300 - ( 25 + x ) = 175
25 + x = 300 - 175
25 + x = 125
x = 125 - 100
x = 25